Teachers Perception of the Use of Social Media in the Learning Process - Darmayanti, Dyan Paramitha (Celebes Journal of Elementary Education, 2023)
Teachers perspectives on incorporating media into the learning process were explored in a study conducted in two schools in Makassar. The study involved 10 participants consisting of subject teachers, principals, technology officers, educators with expertise in social media, and those with knowledge in this area. Data was collected through interviews and group discussions. It was then analysed using the thematic analysis method. The research findings show that social media has the potential to increase student engagement and motivation by enabling interaction and wider access to learning materials. However, there are challenges such as varying levels of technology adoption, concerns over data privacy and student disruption that need to be addressed. To overcome these barriers, the study suggests training for educators to improve their confidence and skills, implementation of privacy protocols to protect student information, creation of relevant and engaging educational content, and establishment of effective monitoring mechanisms to ensure appropriate use of social media in educational settings. By addressing these issues head-on, the benefits of using media in education can be fully utilised.